El Excentrico, 1978-10-05 - Garcia, Bert:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2024)
October 5, 1978 [5 de octubre de 1978]. Ano 29, No 13. Cover contains a portrait of Al Garza, a city councilman who was running for Mayor of San Jose at the time of this issue's release. The headline reads, "Al Garza San Jose City Councilman, Candidate for Mayor."